Application of Compost Produced by Bioconversion of Coffee Husk by Black Soldier Fly Larvae (Hermetia Illucens) as Solid Fertilizer to Lettuce (Lactuca Sativa Var. Crispa) - Suantika, Gede; Putra, Ramadhani Eka; Hutami, Rachmisanti; Rosmiati, Mia (Proceedings of the International Conference on Green Technology, 2017)
Coffee husk is main by product of coffee production and considered has low economic value. Application of this product as feedstuff of insect larvae (i.e. black soldier fly larvae ( Hermetia illucens )) could potencially produce insect biomass and organic solid fertilizer which has significant improved economic value. This study aimed to observe the effect of application of manure, conventional compost of coffee husk, and compost produced by bioconversion activity of black soldier fly larvae to biomass, nitrogen, phosphor, and potassium utilization of lettuce ( Lactuca sativa ). The result showed lettuce cultivated with manure produced significantly highest biomass (62.513 gram) and nitrogen utilization (2.912 gram/kilogram). On the other hand, lettuce cultivated with compost produced by bioconversion had highest phosphor (0.00937 gram/kilogram) and potassium (3.18118 gram/kilogram) utilization. Based on the results, it could be concluded that compost produced by bioconversion process of coffee husk by black soldier fly larvae allowed plant to fulfill their requirement of phosphor and potassium which is considered lack in common Indonesia soil.